2012
DOI: 10.1520/gtj104361
|View full text |Cite
|
Sign up to set email alerts
|

Testing Methane-Hydrate-Saturated Soil Using a Line Dissociation Apparatus

Abstract: The combination of energy source and geohazardous potential of natural gas hydrate has raised the need to understand the processes related to hydrate dissociation within the sediment. In this article, several existing methane hydrate dissociation apparatuses are listed and their sample size capabilities given. A new design for line dissociation tests by combined electrical heating and pressure reduction from a miniature wellbore is presented. The 180-mm-diameter × 225-mm-length hydrate-bearing soil samples can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Three clear trends can be observed from the figure; (1) during initial cooling , in which the temperature gradient is from the sample and outwards (i.e., the confining liquid is cooler than the sample), where a temperature difference of 3.5 was observed, (2) at the final stage of hydrate formation , during which the temperature gradient turns direction, as the sample reaches a stable - low - temperature while the outer cell is affected by the room temperature (even if great thermal isolation efforts are taken), where a temperature difference of was observed, and (3) at hydrate formation initiation , in which the sample temperature spikes as the result of an exothermic reaction to the hydrate formation, where a temperature difference of was observed. Similar temperature difference has been previously reported in the context of thermal gradients even inside the MHBS sample 35 .
Figure 2 ( a ) Temperatures measured by the four thermometers in the system and ( b ) the gas consumption during the hydrate formation process.
…”
Section: Accurate Temperature Measurementssupporting
confidence: 89%
“…Three clear trends can be observed from the figure; (1) during initial cooling , in which the temperature gradient is from the sample and outwards (i.e., the confining liquid is cooler than the sample), where a temperature difference of 3.5 was observed, (2) at the final stage of hydrate formation , during which the temperature gradient turns direction, as the sample reaches a stable - low - temperature while the outer cell is affected by the room temperature (even if great thermal isolation efforts are taken), where a temperature difference of was observed, and (3) at hydrate formation initiation , in which the sample temperature spikes as the result of an exothermic reaction to the hydrate formation, where a temperature difference of was observed. Similar temperature difference has been previously reported in the context of thermal gradients even inside the MHBS sample 35 .
Figure 2 ( a ) Temperatures measured by the four thermometers in the system and ( b ) the gas consumption during the hydrate formation process.
…”
Section: Accurate Temperature Measurementssupporting
confidence: 89%
“…20,21 Falser et al conducted line dissociation tests of MH-saturated soil by combined electrical heating and pressure reduction. 22 The effect of the pore size of the sediments on the dissociation of MH was studied. It was found that the hydrate equilibrium condition was determined by the effect of the pore size on the water activity and that, during the initial stage of hydrate dissociation, the recovery rate of methane was strongly dependent upon the pore size.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier experimental work on hydrate-bearing sand at the National University of Singapore (NUS) had been focusing on developing and testing production schemes of gas from NGH [29][30][31][32][33] . This led on to analysis of fraccability of hydrate-bearing sand, motivated by gas production and the need to understand this complex material property.…”
Section: Application Of Hydraulic Fracturing In Hydrate-bearing Sandmentioning
confidence: 99%